Simulation of use cases of autonomous vehicles - Low, Benedict Ken Z (Nanyang Technological University, 2020)
This paper discusses the use of integrated bus and autonomous vehicle (AV) stops and investigates the effectiveness of three different designs and how they affect the flow of traffic. Furthermore, these designs were also tested with the addition of dedicated AV and bus lanes. These simulations were carried out using the Vissim traffic simulation application. The area surrounding Ang Mo Kio MRT station in Singapore was modelled and used during the simulations. Results suggest that option 1, which resembles a conventional bus stop, is the most effective design in most scenarios. Furthermore, the use of dedicated AV and bus lanes is also indicated to be highly effective in certain instances, namely when traffic is heavy, providing a significant reduction in travel time for AVs and buses, while only increasing the travel time for other vehicles by a much less significant amount.